Traumatic Uterine Rupture in Second Trimester: Two Departments, Two Patients, Two Survivors - Kaggwa H; Deogratious E; Ndiwalana BR; Luweesi H; Kaduyu P (International Journal of Women's Health)
Henry Kaggwa,1 Edemaga Deogratious,2 Billy Richard Ndiwalana,1 Henry Luweesi,2 Paul Kaduyu1 1Department of Obstetrics and Gynecology, Mengo Hospital, Kampala, Uganda; 2Department of Surgery, Mengo Hospital, Kampala, UgandaCorrespondence: Henry Kaggwa, Email kaggwahenry027@gmail.comAbstract: Uterine rupture is defined as the complete division of all three layers of the uterus: the endometrium, myometrium, and perimetrium. Uterine rupture due to trauma often results from high-impact blunt abdominal trauma such as motor vehicle accidents, falls and domestic violence, and it is most common in the third trimester. Prompt diagnosis is necessary to treat this emergency, given its quick onset and progression, to prevent potentially life-threatening complications to the mother and fetus, notably fetal death, which commonly occurs in such cases. Here, we present a case of a 33-year-old female, Gravida 3 Para 2+0, with two previous uterine scars who sustained a traumatic uterine rupture at gestation of 18 weeks due to blunt abdominal trauma after a bathroom fall. The uterine rupture was surgically repaired, allowing continuation of pregnancy and delivery of a live baby 20 weeks later. We demonstrate a timely multidisciplinary approach to managing a pregnant trauma patient by surgical and obstetric teams to optimize outcomes for both the fetus and the mother.Keywords: blunt abdominal trauma, uterine rupture, pregnancy, cesarean delivery